Kepribadian dan Performa Kerja pada Perawat di Tempat Kerja - Danil Haq; Iyus Yosep; Taty Hernawaty (Jurnal Keperawatan Silampari, 2023)
This study aims to describe the relationship between the personality and work performance of nurses in the workplace. The method used is a scoping review with a descriptive approach using three databases, namely CINAHL, Google Scholar, and PubMed. The results showed that four articles discussed the relationship between personality and work performance in nurses. Nurses who know their character can improve optimal work performance. In addition, a job-appropriate nature helps nurses deal with work stress. So that nurses use adaptive coping and have high resilience in dealing with stressors that arise in the workplace. In conclusion, this shows the importance of nurses knowing their personalities to improve work performance in the workplace. Good workplace management can also form an upbeat disposition in achieving goals at work. Keywords: Personality, Nurse, Work performance, Workplace